PENERAPAN BIMBINGAN KELOMPOK DENGAN TEKNIK COGNITIVE RESTRUCKTURING DALAM MENGATASI PROKRASTINASI AKADEMIK SANTRI DI PONDOK PESANTREN AR RAHMAN - ilham; kusnadi; neni noviza (Jurnal At-Taujih, 2024)
This research is entitled "Application of Group Guidance Using Cognitive Restructuring Techniques in Overcoming Academic Procrastination of Palembang Islamic Boarding School Students". This study aims to find out the description of students' academic procrastination and to find out the application of cognitive restructuring techniques in overcoming procrastination at the Ar Rahman Islamic boarding school. This type of research is field research, with a qualitative approach. The subjects of this study were "K" clients, "FW" clients, "NP" clients, "A" clients, and "AKT" clients. Data collection techniques used are observation, interviews, and documentation. While data analysis techniques, data reduction, data presentation, and verification or conclusions. The results of this study indicate that, the picture of procrastination seen from the aspect of not managing time, four subjects are not managing time, only the "FW" client can manage time. From the low self-confidence aspect, four subjects had low self-confidence, only the "FW" client had high self-confidence. From the aspect of considering themselves too busy, four subjects considered themselves too busy, only the "NP" client did not consider himself too busy. From the aspect of stubbornness, the five subjects have stubbornness. From the aspect of manipulating other people's behavior, the five subjects manipulated the behavior of other people. From the aspect of delay as a means of protection for themselves, the five subjects postpone something as a protection for themselves. From the aspect of feeling themselves as victims, the five subjects felt that they were the only ones who were unable to do something. The application of group guidance with cognitive restructuring techniques uses four stages, namely the formation stage, the transition stage, the activity stage, and the termination stage, so that results are obtained, the five clients have experienced a lot of changes, where the five clients can manage time, have higher self-confidence, do not consider self is too busy, not stubborn, does not manipulate the behavior of others, does not use procrastination as a protection to avoid pressure, and does not feel like a victim.